Sex differences in neurodevelopmental and common mental disorders examined from three epidemiological perspectives. (August 2019) - Tesic, Anja; Rodgers, Stephanie; Müller, Mario; Wagner, En-Young N.; von Känel, Roland; Castelao, Enrique; Strippoli, Marie-Pierre F.; Vandeleur, Caroline L.; Seifritz, Erich; Preisig, Martin; Ajdacic-Gross, Vladeta
Highlights: Sex differences in mental disorders are well known but poorly understood. They are negligible regarding age of onset, indicating similar developmental stages. They are noticeable regarding the sex ratio and comorbidity / risk factor patterns. The variation in the sex ratio before puberty requires new attempts at interpretation. Most mental disorders probably require a sex-specific etiopathogenetic understanding. Abstract: Sex differences in neurodevelopmental and common mental disorders are a ubiquitous, well-known, though poorly understood phenomenon. This study examined the issue from three epidemiological perspectives: congruence in age of onset, distribution of sex-ratios with respect to age of onset and similarity of comorbidity and risk factor patterns. The analysis was based on data from the population-based PsyCoLaus study ( N  = 4874, age 35–82 y). Congruence in age of onset and distribution of sex-ratios were examined with the Mann-Whitney test and cluster analysis. The similarity of comorbidity and risk factor patterns, which were represented by 35 variables, was assessed with the Jaccard coefficient and, after factor analysis, with Tucker's congruence coefficient. While age of onset parameters differed little by sex, the sex ratio varied markedly both in early and in late onset disorders. Moreover, the Jaccard coefficients for most disorders indicated that the similarity of comorbidity and further association patterns was low. Similarly, Tucker's congruence coefficient remained below the range of fair similarity in all factor combinations. In sum, sex differences in common mental disorders were impressively reflected by diverging sex ratios and comorbidity / risk factor patterns. This outcome supports the notion that most mental disorders need a sex-specific etiopathogenetic understanding.